EFFECT OF POSITIONING ON BLEEDING COMPLICATION AND LOW BACK PAIN AFTER DIAGNOSTIC CORONARY ANGIOGRAPHY IN PATIENTS WITH CORONARY HEART DISEASE IN AN INTEGRATED HEART CARE CENTER IN INDONESIA - Theresia Febriana Christi Tyas Utami; Diyah Fatmasari; Mardiyono Mardiyono; Shobirun Shobirun (Belitung Nursing Journal, 2018)
Background: Coronary angiography can cause complications of arterial and subcutaneous bleeding (hematoma) and back pain. Changing the position of the patient (positioning) in bed can reduce the pain post-diagnostic catheterization complications. Objective: This study was to examine the effect of positioning on bleeding complication and low back pain after diagnostic coronary angiography in patients with coronary heart disease patient in the Integrated Heart Care Center in Indonesia.Methods: This study was a true-experimental study with randomized posttest-only control group design. Thirty respondents were randomly selected using simple random sampling, which 15 respondents were randomly assigned in the experiment group and control group. The experiment group was given a positioning with 150, 300, 450 head-of-bed elevation in left and right lateral position. An arc tool was used to measure the height of head of bed elevation, a measuring cup to measure arterial bleeding using, a perforated transparent plastic with 5 cm diameter to measure subcutaneous bleeding (hematoma), and Numeric Pain Rating Scale to measure low back pain. Data were analyzed using Kolmogorov- Smirnov and Repeated Measured ANOVA.Results: Findings showed that positioning had no effect on arterial hemorrhage (ρ=1.000) and subcutaneous bleeding (hematoma) (ρ=0.999). Repeated ANOVA test results revealed that positioning had a significant effect on low back pain (ρ=0.017). Conclusion: There was no significant effect of positioning on the occurrence of arterial and subcutaneous bleeding (hematoma), but there was a significant effect in reducing low back pain.